2013
DOI: 10.1007/s11010-013-1792-6
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer potential of rhamnocitrin 4′-β-d-galactopyranoside against N-diethylnitrosamine-induced hepatocellular carcinoma in rats

Abstract: The hepatoprotective activity of flavonoid rhamnocitrin 4'-β-D-galactopyranoside (RGP) obtained from leaves of Astragalus hamosus L. against N-diethylnitrosamine (DENA)-induced hepatic cancer in Wistar albino rats was evaluated. Hepatic cancer in rats was induced by single-dose intraperitoneal administration of DENA (200 mg/kg). Induction of hepatic cancer was confirmed after 7 days of DENA administration by measurement of elevated level of serum α-feto protein (AFP). Administration of DENA in a single dose lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 27 publications
2
15
0
Order By: Relevance
“…In the reviewed articles, flavonoids like Silibinin were shown to be effective in reducing tumor in xenografts mice, acting on p-ERK activation, and reducing their activity [ 40 ]. Other flavonoids showed strong antioxidant activity, reducing stress oxidative markers like MDA [ 19 , 25 , 29 , 31 , 35 ] and stimulating the increase of antioxidant enzymes such as SOD [ 19 , 28 , 29 , 31 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the reviewed articles, flavonoids like Silibinin were shown to be effective in reducing tumor in xenografts mice, acting on p-ERK activation, and reducing their activity [ 40 ]. Other flavonoids showed strong antioxidant activity, reducing stress oxidative markers like MDA [ 19 , 25 , 29 , 31 , 35 ] and stimulating the increase of antioxidant enzymes such as SOD [ 19 , 28 , 29 , 31 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…In human hepatocarcinoma cells SMMC-7721 and HepG2, AF inhibited the growth of tumor cells by arresting cell cycle in the G0/G1 and S phases, inducing apoptosis via mitochondria-dependent and death receptor-dependent apoptotic pathways [ 133 ]. In the hepatic cancer rat model induced by N-diethylnitrosamine, a flavonol glycoside rhamnocitrin 4′-β-d-galactopyranoside can prevent hepatocellular carcinogenesis by increasing the activity of antioxidant enzymes, such as SOD, CAT, GPx, GST and reducing the level of lipid peroxidation [ 134 , 135 ].…”
Section: Anti-aging and Anti-aging Related Effects Of Astragalus Fmentioning
confidence: 99%
“…15 Further research demonstrated that RGP exhibited anticancer potential against Ndiethylnitrosamine-induced hepatic cancer in Wistar rats. 16 Moreover, antioxidant effects of RGP against 6hydroxy (OH)-dopamine-induced oxidative stress in isolated rat brain synaptosomes and its cytoprotective potential in Bendamustine and/or Cyclophosphamide induced toxicity in isolated rat hepatocyte have been proven. 17 Evidence also shows that AH was inadvertently introduced into Australia from Iran, Turkey and Algeria.…”
Section: Introductionmentioning
confidence: 99%